1987
DOI: 10.1099/00221287-133-6-1503
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inactivation of an Extra-cytoplasmic Acid Phosphatase of Yeast-like Cells of Sporothrix schenckii by Sodium Fluoride

Abstract: Suspensions of intact, yeast-like cells of Sporothrix schenckii exhibited an acid phosphatase (EC 3 . 1 .3.2) activity against pnitrophenyl phosphate of about 5 IU (g dry wt)-l, without recourse to membrane perturbation. This extra-cytoplasmic acid phosphatase was reversibly and competitively inhibited by orthophosphate (Ki = 2 mM at pH 5) but unaffected by L( +)-tartrate (in contradistinction to some of the cytoplasmic acid phosphatases of the same organism). Inactivation by NaF of the extra-cytoplasmic isoen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…fluoride was only effective in acidic zone. This finding corroborates the observation of Arnold et al (1987).…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…fluoride was only effective in acidic zone. This finding corroborates the observation of Arnold et al (1987).…”
Section: Discussionsupporting
confidence: 95%
“…The adsorption to lectin (Con A) and the subsequent elution with a-methyl-o-glucoside suggested that the enzyme might be a glycoprotein as reported for other acid phosphatases (Van Etten and Saini 1977;Bhargava and Sachar 1987). Citrate (10 or 100 mM) did not prevent the inhibitory effect of fluoride in contrast to the yeast acid phosphatase (Arnold et al 1987). Phosphonic acid (such as ABP), an analogous compound of phosphate ester, has been shown to be an inhibitor of non-specific acid and alkaline phosphatases and used in affinity chromatography (Landt et al 1978;Dissing et al 1979).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The results from our controls show that NaF itself can be a powerful stimulant of tubule formation, and the rise in tubule frequency when the concentration of NaF was raised from 5 to 20 mM mirrored that seen when com- paring the response to the 5 mM NaF/30 M AlCl 3 and 20 mM NaF/10 M AlCl 3 combinations. We do not know the reason for the response to NaF, but this compound is well known as an inhibitor of many phosphatases, kinases, and ATPases in fungi and other organisms [e.g., Arnold et al, 1987;Pinkse et al, 1999;Vargas et al, 1999], which could directly or indirectly influence tubule-forming activity. It should be noted here that some recent studies reporting the effects of aluminium fluoride on processes possibly regulated by GTP-binding proteins have not checked for non-specific effects of fluorides.…”
Section: Responses To Bfa and Aluminium Fluoridementioning
confidence: 99%
“…At that time, the root cortex was torn with needles to expose the fungal tissue to the staining solution. The effects of 10 mM NaF (acid phosphatase inhibitor (Arnold et al 1987)), 5 mM EDTA and 10 mM KCN (both are alkaline phosphatase inhibitors (Belle, 1972)) on the phosphatase activity in the hyphae were also examined. Acid and alkaline phosphatase activities in the fungal tissue were identified by the azo dye method (Tisserant et al, 1993).…”
Section: Methodsmentioning
confidence: 99%